What Makes a Good Trader? On the Role of Intuition and Reflection on Trader Performance - CORGNET, BRICE; DESANTIS, MARK; PORTER, DAVID (Journal of Finance, 2018)
ABSTRACT Using laboratory experiments, we provide evidence on three factors influencing trader performance: fluid intelligence, cognitive reflection, and theory of mind (ToM). Fluid intelligence provides traders with computational skills necessary to draw a statistical inference. Cognitive reflection helps traders avoid behavioral biases and thereby extract signals from market orders and update their prior beliefs accordingly. ToM describes the degree to which traders correctly assess the informational content of orders. We show that cognitive reflection and ToM are complementary because traders benefit from understanding signals’ quality only if they are capable of processing these signals.